2019
DOI: 10.1002/solr.201900209
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Planar Perovskite Solar Cells via a Sputtered Cathode

Abstract: Perovskite solar cells (PSCs) attract great attention due to their low cost and high efficiency. In general, the Au cathode, a key component in PSCs, is prepared via an uneconomic vacuum thermal deposition method. Instead, the sputtering deposition method is much more economic and faster. However, it is generally thought that the organic hole transport layer such as 2,2′,7,7′‐tetrakis[N,N‐di(4‐methoxyphenyl)amino]‐9,9′‐spirobifluorene (Spiro‐OMeTAD) can be easily damaged by the high energy plasma during the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
(30 reference statements)
2
23
0
Order By: Relevance
“…Magnetron sputtering is a mature and reliable technique for lab-and industrial-scale fabrication of metal-oxide ESLs and thin films due to its distinct advantages such as high quality and uniform deposition, strong adhesion between film layers, fine control of film density and thickness, high deposition yield, and relatively low operational cost. [190][191][192] Despite these advantages, sputtering has been rarely investigated so far for SnO 2 processing for PSCs, and only one study reported PCEs values >20% for a 0.09 cm 2 cell. [193] The authors also reported a PCE of 12.03% for mini-modules (aperture area of 22.8 cm 2 ).…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…Magnetron sputtering is a mature and reliable technique for lab-and industrial-scale fabrication of metal-oxide ESLs and thin films due to its distinct advantages such as high quality and uniform deposition, strong adhesion between film layers, fine control of film density and thickness, high deposition yield, and relatively low operational cost. [190][191][192] Despite these advantages, sputtering has been rarely investigated so far for SnO 2 processing for PSCs, and only one study reported PCEs values >20% for a 0.09 cm 2 cell. [193] The authors also reported a PCE of 12.03% for mini-modules (aperture area of 22.8 cm 2 ).…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…Besides, the deposition process is usually operated in a high vacuum chamber, leading to high repeatability with minor damage to the natural environment. 147 Qiu and co-workers systematically investigated the chemical and physical characteristics of sputtered SnO 2 . It played a signicant role in the formation of high quality to control the oxidizing process.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…Despite many efforts in establishing wide-scale deposition of contact technologies with industrial standards methods such as sputtering for perovskite transport layers [230][231][232][233][234][235], stagnating issues of stability and hysteresis remain major concerns [236][237][238]. Similarly, the co-evaporation deposition technique in Ref.…”
Section: Future Perspectives Towards Large-scale Industrializationmentioning
confidence: 99%